Reconstruction of Regulation of the Authority to Address Determination of Village Head Election Results as the Object of State Administrative Object of State Administrative Disputes Based on Justice Value - Bernat Panjaitan; Anis Mashdurohatun; Sri Kusriyah (International Journal Labs, 2023)
The State of Indonesia is a State of Law